2014
DOI: 10.1007/s00520-014-2516-5
|View full text |Cite
|
Sign up to set email alerts
|

Fear of progression in patients 6 months after cancer rehabilitation—a validation study of the fear of progression questionnaire FoP-Q-12

Abstract: The FoP-Q-12 proved to be a valid instrument for measuring fear of progression in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
8
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 28 publications
7
70
8
4
Order By: Relevance
“…Differences regarding objective medical data and other clinical characteristic such as the presence of complications like CF-related diabetes or chronic colonization with germs could be assumed. It is known that FoR in patients with cancer differs regarding the clinical characteristics, such as disease severity or form of therapy [52,53]. The small subsample of fathers also limits representativeness of our results regarding gender.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences regarding objective medical data and other clinical characteristic such as the presence of complications like CF-related diabetes or chronic colonization with germs could be assumed. It is known that FoR in patients with cancer differs regarding the clinical characteristics, such as disease severity or form of therapy [52,53]. The small subsample of fathers also limits representativeness of our results regarding gender.…”
Section: Discussionmentioning
confidence: 97%
“…The measure developed for partners [16], which is based on the short form of the FoP questionnaire [3] also revealed more than one factor, as well as further psychometric testing of the short form for patients [52], but finally a one-factor solution was chosen. Although the generation of the short-form was made via EFA and our item pool was generated using clinical judgment, which might entailed the explicit selection of items from the original measure [4] representing the most likely consequences for the parents' lives as well, comparable psychometric results were found.…”
Section: Discussionmentioning
confidence: 99%
“…The German version of the FoP-Q-SF is validated in cancer patients and is a reliable instrument, and a total sum score (higher values indicate higher levels of fear of progression) without a standardized cutoff score for clinically relevant level of fear of progression [32, 33]. The questionnaire is administered to participants at baseline (T1) and follow-up (T2).…”
Section: Methodsmentioning
confidence: 99%
“…Fear of cancer recurrence (FCR) is a problem that almost all cancer survivors experience. Traditionally, FCR has been defined as the fear that cancer could return or progress in the same place or in another part of the body . FCR is one of the most prevalent psychological burdens experienced by cancer patients and survivors, with previous researches reporting prevalence rates of FCR ranging between 33% and 97%.…”
Section: Introductionmentioning
confidence: 99%
“…In recently published studies, a variety of factors were found to be associated with the cancer patients’ FCR level. Demographic characteristics such as female gender, young age, living apart or divorce, a higher level of education, and no children have been reported to be related to higher FCR.…”
Section: Introductionmentioning
confidence: 99%